Investigation of strategic capacity issues in the aerospace sector - Wang, King; Buxton, David; Farr, Richard; MacCarthy, Bart (VIVACE project consortium, 2007)
The business environment is changing fast and radically. Traditional capacity planning has limitations in today’s dynamic environments, particularly from a strategic perspective in the aerospace sector. This document sets out to identify the unique characteristics of the aerospace industry and compare the traditional views of capacity planning and modern concepts in SCP relevant to the sector. Key findings are summarised from an analysis of the literature on strategic capacity planning. The importance of considering demand uncertainty, technology uncertainty and supply uncertainty is highlighted. Two case studies in the aero- engine sector are presented. A collaborative virtual organisation requires Strategic Capacity Planning (SCP) that focuses not only on economies of scale but also on coordination, flexibility and responsiveness. An integrated framework for addressing SCP in the aerospace industry is presented.